What Can We Learn From the Grenfell Tower Disaster?: Priorities for Sustainable Change - Hywel Davies (Journal of Sustainable Design and Applied Research in Innovative Engineering of the Built Environment, 2018)
The catastrophic fire at Grenfell Tower on 14 June 2017 killed 72 people and shocked the world. It also changed many more lives forever. As well as the police and public inquiries, which are ongoing, it led to an independent review of Building Regulations and Fire Safety, led by Dame Judith Hackitt, a Chartered Engineer and Fellow of the Royal Academy of Engineering. Her review, and the associated activity around building regulations in England, is the most significant review in over a generation, since the 1984 Building Act, and is widely recognised as being a once in two generations opportunity to reform building regulations in England. It will also have implications in Wales, Scotland and Northern Ireland, which are watching closely. Moreover, it will extend beyond building regulations, which apply up until a building is complete and handed over, into the operation of the building and subsequent maintenance and minor works. This review activity is being watched closely outside the UK too, with three states in the Australian Commonwealth introducing legislation related to cladding on tall buildings in October 2018.